TEKNIK IRON BLANKET PADA ECOPRINT MENGGUNAKAN PEWARNA ALAM - Tsani, Romadhona (Universitas Negeri Surabaya, 2024)
ABSTRACT Ecoprint is a fabric printing technique by transferring colors and plant shapes or patterns onto textiles. One technique for making ecoprints is an iron blanket, which is a technique for making ecoprints by stacking or covering the ecoprint media with cloth that has been given natural dye first. The iron blanket technique has become popular among artists and craftsmen, because it produces unique and environmentally friendly fabric. The use of organic materials from nature also supports the manufacture of sustainable textiles, namely the manufacture of textiles that minimize negative impacts on the environment. One of the important elements in printing textiles with natural colors is plants that have dyes in them. Natural dyes do not produce waste that can harm the surrounding environment, because the nature of natural dyes is non-toxic and easily decomposed. In this study, natural dyes were made using terminalia cattapa/ketapang leaves, ricinus communis linn leaves and psidium guajava leaves. This plant is easy to find, but is usually only used as a shrub or as an ornamental plant. These three plants produce a grayish green color with alum fixator, and produce a grayish brown color with alum fixator.